2022
DOI: 10.1038/s41598-022-25049-w
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised adaptation of an ECoG based brain–computer interface using neural correlates of task performance

Abstract: Brain–computer interfaces (BCIs) translate brain signals into commands to external effectors, and mainly target severely disabled users. The usability of BCIs may be improved by reducing their major constraints, such as the necessity for special training sessions to initially calibrate and later keep up to date the neural signal decoders. In this study, we show that it is possible to train and update BCI decoders during free use of motor BCIs. In addition to the neural signal decoder controlling effectors (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…It was applied in real time for closed-loop adaptation of 3D hand translation/wrist rotation decoders in tetraplegics (Benabid et al, 2019 ; Moly et al, 2022 ). Finally, REW-NPLS was tested in the simulation of auto-adaptive continuous (bi-directional cursor control) and discrete multiclass motor imagery (MI) BCI in a tetraplegic patient (Rouanne et al, 2022 ). In the (Sliwowski et al, 2022 ) offline study, ANN algorithms were reported to outperform the REW-NPLS decoder.…”
Section: Methodsmentioning
confidence: 99%
“…It was applied in real time for closed-loop adaptation of 3D hand translation/wrist rotation decoders in tetraplegics (Benabid et al, 2019 ; Moly et al, 2022 ). Finally, REW-NPLS was tested in the simulation of auto-adaptive continuous (bi-directional cursor control) and discrete multiclass motor imagery (MI) BCI in a tetraplegic patient (Rouanne et al, 2022 ). In the (Sliwowski et al, 2022 ) offline study, ANN algorithms were reported to outperform the REW-NPLS decoder.…”
Section: Methodsmentioning
confidence: 99%
“…While offline experiments on pre-recorded data are commonly used to evaluate neural decoder performance, they do not always correlate well with performance in an online, closed-loop setting [24][25][26]. In a closed loop environment, the output of the BMI is fed directly to the output device, allowing the user to attempt to correct for any errors in the BMI output in real time.…”
Section: Closed Loop Experimentsmentioning
confidence: 99%
“…In the first experiment, 30 out of 46 input neurons were removed after 50 reaches. This simulates a loss of connection to neurons that is common in real BMI systems due to electrodes shifting or becoming damaged [24,49]. The continuous learning SNN was allowed to train using continuous learning for 30 subsequent reaches, while the other decoders were recalibrated on neural data from the first 30 reaches after reassignment.…”
Section: Neural Variability and Disruptionsmentioning
confidence: 99%
See 2 more Smart Citations